The In Vitro Antibiofilm Activity of Water Leaf Extract of Papaya (Carica papaya L.) against Pseudomonas aeruginosa - Ekajayanti Kining; Syamsul Falah; Novik Nurhidayat (IPB University, 2015)
Pseudomonas aeruginosa is one of opportunistic pathogen forming bacterial biofilm. The biofilm sustains the bacterial survival and infections. This study aimed to assess the activity of water extract of papaya leaves on inhibition of cells attachment, growth and degradation of the biofilm using crystal violet (CV) biofilm assay. Research results showed that water extract of papaya leaves contains alkaloids, tanins, flavonoids, and steroids/terpenoids and showed antibacterial activity and antibiofilm against P. aeruginosa. Addition of extract can inhibit the cell attachment and was able to degrade the biofilm of 40.92% and 48.058% respectively at optimum conditions: extract concentration of 25% (v/v), temperature 37.5 °C and contact time 45 minutes. With a concentration of 25% (v/v), temperature of 50 °C and the contact time of 3 days, extract of papaya leaves can inhibit the growth of biofilms of 39.837% v/v.